2002
DOI: 10.1210/en.143.2.596
|View full text |Cite
|
Sign up to set email alerts
|

Intracrine PTHrP Protects against Serum Starvation-Induced Apoptosis and Regulates the Cell Cycle in MCF-7 Breast Cancer Cells

Abstract: PTHrP is secreted by breast cancer cells in vivo and in vitro. In the breast cancer cell line MCF-7, PTHrP overexpression is associated with increased mitogenesis. We used this cell line to study the mechanism for the proliferative effects of PTHrP. Clonal MCF-7 lines were established overexpressing wild-type PTHrP or PTHrP mutated in the nuclear localization signal (NLS). Mutation of the NLS negated the proliferative effects and nuclear trafficking of PTHrP, indicating that increased mitogenesis is mediated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 0 publications
11
54
0
3
Order By: Relevance
“…The recent report by Tovar Sepulveda et al (2002), focused on PTHrP and MCF-7, is particularly instructive here, although it does not meet the question of the different response to PTHrP by the same cell. They clearly demonstrated that PTHrP possesses a double signalling on MCF-7: an antimitogenic pathway mediated by the membrane receptor and a second wave of signalling, pro-proliferative and antiapoptotic, based on nuclear localisation of the peptide.…”
Section: Sirmentioning
confidence: 95%
See 1 more Smart Citation
“…The recent report by Tovar Sepulveda et al (2002), focused on PTHrP and MCF-7, is particularly instructive here, although it does not meet the question of the different response to PTHrP by the same cell. They clearly demonstrated that PTHrP possesses a double signalling on MCF-7: an antimitogenic pathway mediated by the membrane receptor and a second wave of signalling, pro-proliferative and antiapoptotic, based on nuclear localisation of the peptide.…”
Section: Sirmentioning
confidence: 95%
“…However, we can realise that in May 2002, the date of the first submission, the author could not have read the paper by Tovar Sepulveda et al (2002). On the contrary, Hoey knew and cited the work by Falzon and Du (2000).…”
Section: Sirmentioning
confidence: 99%
“…This approach is in line with the work by other authors to obtain a detectable effect of PTHrP and its fragments in in vitro studies. (19,41,57) In conclusion, we have identified novel pathogenetic functions of PTHrP in MM related to tumor survival, proliferation, and OC hyperactivation. Because serum elevation of PTHrP in patients with solid tumors produces severe skeleton devastation and leads to a poor prognosis, a systematic analysis of PTHrP levels in MM patients would be advisable, to determine whether this peptide is a novel marker of disease progression.…”
Section: Discussionmentioning
confidence: 81%
“…(19) Other authors, however, have suggested that, to induce a similar effect, the NLS subunit may be transported and internalized in nuclei by cytoplasmic importin-b and that this mechanism is protective for tumor cells in preventing their apoptosis or anoikis induced by starvation. (41,42,46) By contrast, an opposite proapoptogenic effect has been ascribed to the NLS þ mid-region (aa 38-94) in cell kinetic analysis in breast cancer. (47) We demonstrated in MM cells a definite proliferative effect of this subunit in the serum starvation culture condition and we assumed that starved cells are capable of progressively activating several cytoplasmic transporters, such as importin-b, to localize the NLS fragment in nuclei for their own cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation